Correlations between body length and otolith size in smallmouth bass Micropterus dolomieu Lacépède, 1802 with implications for retrospective growth analyses. (25th May 2015) - Humston, R.; Moore, M.; Wass, C.; Dennis, D.; Doss, S.
Summary Reconstructing individual growth history from analysis of increments in otoliths, scales, or spines can provide information on past growth responses to environmental variation, which in turn can be useful for predicting population‐level response to climate change. The objective of this study was to examine correlations between body length and different metrics of otolith size for Micropterus dolomieu. Three metrics corresponding to commonly‐used microstructural and ultrastructural otolith dimensions were measured using image analysis of digital micrographs from a sample of 214 M. dolomieu ranging from 115 to 438 mm total length collected in 2011–2013. It was found that anteroposterior length of whole otoliths provided much improved regression relationships with body size as well as ease of data collection and faster sampling throughput compared with microstructural measures from polished sections. When applying these metrics to reconstruct growth history the biological intercept model generally produced more reasonable back‐calculated estimates of length‐at‐age, although this was not consistent across all otolith metrics. Results suggest that whole otolith measures should be employed due to efficiency of data collection and greater reliability for reconstructing growth history in M. dolomieu.